2014
DOI: 10.1007/s11136-014-0628-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of concurrent granulocyte–macrophage colony-stimulating factor on quality of life in head and neck cancer patients: results of the randomized, placebo-controlled Radiation Therapy Oncology Group 9901 trial

Abstract: Purpose The Radiation Therapy Oncology Group (RTOG) conducted a randomized, placebo-controlled, trial evaluating the efficacy of GM-CSF in reducing mucosal injury and symptom burden from curative radiotherapy for head-and-neck (H&N) cancer. Methods Eligible patients with H&N cancer receiving radiation encompassing ≥ 50% of the oral cavity or oropharynx received subcutaneous GM-CSF or placebo. Quality of life (QoL) was assessed using the RTOG modified University of Washington H&N symptom questionnaire at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Various attempts to reduce radiation toxicity regarding mucosal appears to provide little improvement in patient-reported symptoms, which sometimes differs from the clinician's judgment on symptom relief [35]. In a group of patients undergoing septoplasty, the mean 15D score worsened 6 months after surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…Various attempts to reduce radiation toxicity regarding mucosal appears to provide little improvement in patient-reported symptoms, which sometimes differs from the clinician's judgment on symptom relief [35]. In a group of patients undergoing septoplasty, the mean 15D score worsened 6 months after surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, the oncologic treatment method is described: chemotherapy [2], combined chemotherapy and radiotherapy [3,10,11], radiotherapy [11], chemotherapy [12,13,14], combined chemotherapy and radiotherapy [15,16], radiotherapy [17,18], combined chemotherapy and radiotherapy [18], chemotherapy [19], combined chemotherapy and radiotherapy [20], radiotherapy [20], chemotherapy [21], combined chemotherapy and radiotherapy [22,23], radiotherapy [24], combined chemotherapy and radiotherapy [25], radiotherapy [26], combined chemotherapy and radiotherapy [27], chemotherapy [28]. …”
Section: Methodsmentioning
confidence: 99%
“…A recent meta‐analysis of nine randomised clinical trials including 2197 patients (filgrastim, n= 1130; placebo or no treatment, n = 1067) showed that the use of filgrastim led to a decrease in FN incidence (relative risk [RR] 0.63, 95% CI 0.53‐0.75), a result further confirmed in two observational studies . A meta‐analysis of five randomised clinical trials and one non‐randomised clinical trial with a total of 1409 patients (filgrastim, n = 714; placebo or no treatment, n = 695) reported a decreased incidence in grade 3/4 neutropenia with filgrastim (RR 0.50, 95% CI 0.37‐0.68) …”
Section: Discussionmentioning
confidence: 93%